(untitled) (Journal of Misan Researches, 2023)
This study explains the nature of diplomacy between the United States of America and Bulgaria, which began in 1903, and was suspended from 1941 to 1947, but after several problems that the United States made with Bulgaria in 1950, as the latter began attempts to restore relations, which culminated in its return in 1959, but the commission was not opened until 1960, and despite the return of relations, they were not at a good level of development and stability, especially after hampering the process of settling US financial claims, and Bulgaria’s demands to obtain the rights of the first commercial sponsorship state, but what most affected the stability of that relationship Bulgarian reactions to the crises that occurred during 1961, including harassment of representatives of the diplomatic mission of the Commission in Washington, as well as because of the American operation against Cuba by the United States in the name of (the Bay of Pigs) and the Berlin Wall crisis, as well as during 1962, which exposed The American delegation in Sofia led to several angry demonstrations due to the missile crisis in Cuba, to calm relations with the death of US President John F. Kennedy in 1963.